الصناعات التحويلية للتمور - العبد، محمد مصطفى راضي (الهيئة العربية للاستثمار والانماء الزراعي, 2006)
إن إنتاج مواد ذات قيمة مضافة من خلال صناعات التمور التحويلية يمكن استخدامها في الصناعات الغذائية والصيدلانية والكيماوية وخاصة عندما تكون مادتها الأولية من التمور رديئة النوعية سيساهم إلى حد كبير في دعم اقتصاديات نخيل التمر. في هذه الصناعات يحول السكر وهو المكون الرئيسي في التمور إلى مواد أخرى، بواسطة وسائل فيزياوية -كيمياوية وتقنية حياتية. الدراسة الحالية تستعرض معظم صناعات التمور التحويلية كإنتاج الشراب الغني بالفركتوز ومسحوق الفركتوز والكلوكوز والكحولات المتعددة وحامض الستريك والكحول الاثيلي والخل وخميرة الخبز، بالإضافة إلى الملاحظات الفنية المفيدة لتحوير مثل هذه الصناعات لجعلها موائمة للإنتاج المعتمد على عصير التمر مع مسح لأحدث المعلومات السوقية المتوفرة لكل مادة يزمع إنتاجها. توصي الدراسة بالاهتمام بالصناعات التحويلية ونشرها من خلال توصيات محددة وبناء عليه يقترح مخطط مبتكر ومتكامل للصناعات المشار إليها أعلاه يتم الاستفادة من خلاله من وحدات العمل المشتركة وذلك لخفض تكاليف الإنتاج كاستخلاص عصير التمر وتنقيته وتكييفه علما بأن مادة الدراسة أعدت بناء على أحدث المصادر ذات العلاقة بالإضافة إلى الاتصالات الشخصية. Dates transmutation industries provide opportunities to produce added value products that can be used as ingredients for food, pharmaceutical and chemical industries especially from low quality dates and, thus, boost the economy of date palm cultivation. These industries convert the main component of dates, which is sugar, by mean of physical, chemical, and biotechnological methods to produce assorted ingredients. The current study focuses on the dates derived industries such as production of high fructose syrup (HFCS), crystalline glucose and fructose, polyols, citric acid, ethanol, vinegar and baker's yeast. Furthermore, the study includes useful technical comments on the modifications of similar industry, which manufacture different raw material, to suit the dates extract as feedstock. In addition, a brief overview of the market of each product has been incorporated according to the latest available data. The study emphasises the implementation of the date derived industries through definite recommendations. Accordingly, a novel design is recommended throughout the study in which common units of operation for instance extraction, purification and juice conditioning are integrated in an industry complex to reduce the cost of operation. However, the up to date subject matter of of the study has been prepared by rigorous literature search and personal communications.
ملخص لبحث منشور باللغة الإنجليزية
Keywords: تكاليف الإنتاج -- إنتاج التمور -- صناعة التمور -- الصناعات التحويلية -- الصناعات الغذائية -- الصناعات الكيميائية -- عصير التمور -- التكنولوجيا الصناعية -- زراعة النخيل